Popular culture and the end of antiquity in southern Gaul, c. 400-550 - Grig, Lucy (Cambridge University Press, 2024)
This book offers a new look at the transformation of the classical world in Late Antiquity. It focuses on a particular region, rich in both archaeological and literary evidence, and examines the social, cultural and religious history of late antique southern Gaul through the lens of popular culture. Using material culture, comparative and theoretical material alongside the often dominant normative and prescriptive texts produced by the late antique church, Lucy Grig shines a fresh light on the period. She explores city and countryside alike as contexts for late antique popular culture, and consider a range of case-studies, including the vibrant late antique festival of the Kalends of January. In this way important questions of continuity, change and historical agency are brought to the fore. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.